Museum Genomics Illuminate the High Specificity of a Bioluminescent Symbiosis for a Genus of Reef Fish - Gould, Alison L.; Fritts-Penniman, Allison; Gaisiner, Ana (Frontiers in Ecology and Evolution, 2021)
Symbiotic relationships between bioluminescent bacteria and fishes have evolved multiple times across hundreds of fish taxa, but relatively little is known about the specificity of these associations and how conserved they have been through time. This study describes the degree of specificity of a bioluminescent symbiosis between cardinalfishes in the genus Siphamia and luminous bacteria in the Vibrio family. Primarily using museum specimens, we investigate the co-divergence of host and symbiont and test for patterns of divergence that correlate with both biogeography and time. Contrary to expectations, we determined that the light organ symbionts of all 14 Siphamia species examined belong to one genetic clade of Photobacterium mandapamensis (Clade II), indicating that the association is highly specific and conserved across the host genus. Thus, we did not find evidence of codivergence among hosts and symbionts. We did observe that symbionts hosted by individuals sampled from colder water regions were more divergent, containing more than three times as many single nucleotide polymorphisms than the rest of the symbionts examined. Overall our findings indicate that the symbiosis between Siphamia fishes and P. mandapamensis Clade II has been highly conserved across a broad geographic range and through time despite the facultative nature of the bacterial symbiont. These results suggest that this bioluminescent symbiosis could have played a key role in the evolution of the host genus and that there are conserved mechanisms regulating its specificity that have yet to be defined.